Ethical considerations for remote sensing and open data in relation to the endangered archaeology in the Middle East and North Africa project. Issue 3 (24th March 2021) - Fisher, Michael; Fradley, Michael; Flohr, Pascal; Rouhani, Bijan; Simi, Francesca
Abstract: The UK‐based Endangered Archaeology in the Middle East and North Africa (EAMENA) project uses remote sensing techniques to rapidly record and evaluate the status of archaeological and cultural heritage sites in the MENA region. Applying remote sensing methods to the archaeological landscapes of 20 countries, EAMENA is one of the largest documentation projects of its kind. Such a scope raises important ethical questions fundamental to the practice of remote‐sensed archaeology, and this paper contributes to this discussion by reflecting on EAMENA's unique role in this subfield. We present ethical issues and possible solutions related to remote sensing and archaeology, drawing on models developed within the humanitarian aid sector and postcolonial archaeology. In addition, we consider issues of national sovereignty and their relationship to the engagement of local communities. Finally, this paper examines the roles of data openness and open access policies as ethical factors and how EAMENA has addressed these so far.